Relationship Between Coefficient and Compressibility of Carbenium Ion Hydrolysis Rate - NOORIZADEH, S. (Asian Journal of Chemistry, 2010)
A linear relationship between the rate constant of hydrolysis and a recently introduced parameter, group compressibility of a series of proposed carbenium ions (28 ions) are shown as log kw = 17.00224– 4.28332Gβ′. According to these group compressibilities, a new substituent constants, σp (Gβ′), are also introduced, which correctly explains the experimental electrophilicity ordering established in terms of experimental scales.